DOI: 10.11606/d.18.2018.tde-30102018-100423
|View full text |Cite
|
Sign up to set email alerts
|

Análise do comportamento dinâmico de ponte de concreto por meio de filtragem de sinais GPS

Abstract: Aqui expresso minha gratidão àqueles que contribuíram de forma direta ou indireta para o andamento e término desta pesquisa de mestrado. Ao meu Deus, que não me deixou perder a fé e fraquejar nos momentos difíceis deste trabalho. A professora Dra. Ana Paula Camargo Larocca pela valiosa oportunidade da orientação, amizade, preocupação, motivação, paciência e pela confiança depositada para o desenvolvimento deste trabalho, que me permitiu desenvolver pessoal e profissionalmente. Ao professor Dr. João Olympio de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…After conducting a thorough examination of the available data on frequency settings for small-and medium-span beam bridges both domestically and internationally, it has been observed that there is a scarcity of research in this area. The analysis of the data can be summarized as follows: Stiros et al [9] tested the structural dynamic characteristics of Gorgopotamos bridge, and calculated that the midspan deflection of the structure caused by heavy freight trains crossing the bridge is about 6 mm and the frequency range of the structure is between 3.18 and 3.63 Hz; José Venâncio Marra de Oliveira [10,11] used a 100 Hz GPS to dynamically monitor a small concrete bridge, and used a CWT-Morlet filter to provide accurate position transient signal and report the fundamental frequency of the structure at the same time. The filtered data were displayed on the identification scale diagram, and it was found that the confidence level was 95.0% and the frequency range was 0.1 to 50 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…After conducting a thorough examination of the available data on frequency settings for small-and medium-span beam bridges both domestically and internationally, it has been observed that there is a scarcity of research in this area. The analysis of the data can be summarized as follows: Stiros et al [9] tested the structural dynamic characteristics of Gorgopotamos bridge, and calculated that the midspan deflection of the structure caused by heavy freight trains crossing the bridge is about 6 mm and the frequency range of the structure is between 3.18 and 3.63 Hz; José Venâncio Marra de Oliveira [10,11] used a 100 Hz GPS to dynamically monitor a small concrete bridge, and used a CWT-Morlet filter to provide accurate position transient signal and report the fundamental frequency of the structure at the same time. The filtered data were displayed on the identification scale diagram, and it was found that the confidence level was 95.0% and the frequency range was 0.1 to 50 Hz.…”
Section: Introductionmentioning
confidence: 99%